Granzyme B in Inflammatory Diseases: Apoptosis, Inflammation, Extracellular Matrix Remodeling, Epithelial-to-Mesenchymal Transition and Fibrosis - Velotti, Francesca; Barchetta, Ilaria; Cimini, Flavia Agata; Cavallo, Maria Gisella (Frontiers in Immunology, 2020)
Inflammation is strictly interconnected to anti-inflammatory mechanisms to maintain tissue homeostasis. The disruption of immune homeostasis can lead to acute and chronic inflammatory diseases, as cardiovascular, pulmonary, metabolic diseases and cancer. The knowledge of the mechanisms involved in the development and progression of these pathological conditions is important to find effective therapies. Granzyme B (GrB) is a serine protease produced by a variety of immune, non-immune and tumor cells. Apoptotic intracellular and multiple extracellular functions of GrB have been recently identified. Its capability of cleaving extracellular matrix (ECM) components, cytokines, cell receptors and clotting proteins, revealed GrB as a potential multifunctional pro-inflammatory molecule with the capability of contributing to the pathogenesis of different inflammatory conditions, including inflammaging, acute and chronic inflammatory diseases and cancer. Here we give an overview of recent data concerning GrB activity on multiple targets, potentially allowing this enzyme to regulate a wide range of crucial biological processes that play a role in the development, progression and/or severity of inflammatory diseases. We focus our attention on the promotion by GrB of perforin-dependent and perforin-independent (anoikis) apoptosis, inflammation derived by the activation of some cytokines belonging to the IL-1 cytokine family, ECM remodeling, epithelial-to-mesenchimal transition (EMT) and fibrosis. A greater comprehension of the pathophysiological consequences of GrB-mediated multiple activities may favor the design of new therapies aim to inhibit different inflammatory pathological conditions such as inflammaging and age-related diseases, EMT and organ fibrosis.